Village doctors' dilemma in China: A systematic evaluation of job burnout and turnover intention - Chen, Yuquan; You, Yanwei; Shen, Yaying; Du, Zifei; Dai, Tao (Frontiers in Public Health, 2022)
Background Village doctors (VDs) in China undertook arduous primary healthcare missions. However, they received little attention in comparison to doctors in urban public secondary and tertiary hospitals. There is an urgent need to explore the overall situation of turnover intention and job burnout among VDs to evaluate and adjust current health manpower policy. Methods In this study, seven databases like PubMed, EMBASE, Web of Science (WOS), WanFang, China Science and Technology Journal Database (VIP), Chinese BioMedical Literature Database (CBM), and China National Knowledge Infrastructure (CNKI) were systematically searched, relevant experts were consulted, and empirical research on job burnout and turnover intention among VDs in international publications was evaluated. Therefore, we evaluated the prevalence of job burnout among VDs in general, across all dimensions and different severity levels, as well as the scores of each category. For turnover intention, we assessed the prevalence of different groups and their overall situation and also identified significant contributors. Results In this study, we integrated 20 research evidences on job burnout and turnover intention among 23,284 VDs from almost all provinces in China, and the prevalence of turnover intention among VDs in China was as high as 44.1% [95% confidence interval (CI): 34.1–54.2], which was two to four times that of primary health workers in high-income countries, but not much different from some developing countries. Simultaneously, VDs with the highest risk of turnover intention were men [odds ratio (OR): 1.22 (1.05–1.43)], those with a monthly income below USD 163.4 [OR: 0.88 (0.78–0.98)], those with a high educational level [OR: 0.88 (0.78–0.98)], and those <40 years old [OR: 1.27 (1.16–1.40)]. Similarly, the detection rate of job burnout toward them was 59.8% (95% CI: 38.7–79.1) with the MBI-GS score being 44.44 (95% CI: 37.02–51.86) in a total of 90, while the detection rate of job burnout in moderate and above almost reached 20%. The most significant contributor that affects job burnout was low personal accomplishment (LPA), and the detection rate for moderate and higher severity was 65.2% (95% CI: 58.7–71.7). Conclusion Attention should be paid to the high turnover intention and severe job burnout of primary health workers in rural areas of developing countries, and targeted measures should be taken to improve the situation. Health policymakers should increase financial subsidies for VDs, set a reasonable workload, improve various health policies such as pension insurance for VDs, and encourage “targeted training” for medical students to enrich and expand their team. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42021289139.